Effective anti-adhesives of uropathogenic Escherichia coli - Ribić Rosana; Meštrović Tomislav; Neuberg Marijana; Kozina Goran (Acta Pharmaceutica)
Urinary tract infections (UTIs) caused by uropathogenic Escherichia coli (UPEC) are among the most common infectious diseases in humans. Due to their frequent occurrence in the community and nosocomial settings, as well as the development of resistance to the commonly prescribed antimicrobial agents, an enormous financial burden is placed on healthcare systems around the world. Therefore, novel approaches to the prevention and treatment of UTIs are needed. Although UPEC may harbour a plethora of virulence factors, type I fimbriae and P pili are two of the most studied adhesive organelles, since the attachment to host cells in the urinary tract is a crucial step towards infection. Design of receptor analogues that competitively bind to UPEC surface adhesins placed at the top of pili organelles led to the development of anti-adhesive drugs that are increasingly recognized as important and promising alternatives to antibiotic treatment of UTIs.